Predictors of Treatment Resistance Across Different Clinical Subtypes of Depression: Comparison of Unipolar vs. Bipolar Cases - Fornaro, Michele; Fusco, Andrea; Novello, Stefano; Mosca, Pierluigi; Anastasia, Annalisa; De Blasio, Antonella; Iasevoli, Felice; de Bartolomeis, Andrea (Frontiers in Psychiatry, 2020)
Objective: Treatment-resistant depression (TRD) and treatment-resistant bipolar depression (TRBDe) poses a significant clinical and societal burden, relying on different operational definitions and treatment approaches. The detection of clinical predictors of resistance is elusive, soliciting clinical subtyping of the depressive episodes, which represents the goal of the present study. Methods: A hundred and thirty-one depressed outpatients underwent psychopathological evaluation using major rating scales, including the Hamilton Depression Rating, which served for subsequent principal component analysis, followed-up by cluster analysis. Results: The cluster analysis identified two clinically interpretable, yet distinctive, groups among 53 bipolar (resistant cases=15, or 28.3%) and 78 unipolar (resistant cases=20, or 25.6%). Among MDD patients, cluster “1” included the following components: “Psychic symptoms, depressed mood, suicide, guilty, insomnia” and “genitourinary, gastrointestinal, weight loss, insight”. Altogether, with broadly defined “mixed features”, this latter cluster correctly predicted treatment outcome in 80.8% cases of MDD. The same “broadly-defined” mixed features of depression (standard diagnostic and statistical manual for mental disorders, fifth edition - DSM-5 - specifier plus increased energy, psychomotor activity, irritability) correctly classified 71.7% of BD cases, either as TRBDe or not. Limitations: Small sample size and high rate of comorbidity. Conclusions Although relying on different operational criteria and treatment history, TRD and TRBDe seem to be consistently predicted by broadly defined mixed features among different clinical subtypes of depression, either among unipolar or bipolar cases. If replicated by upcoming studies to encompass also biological and neuropsychological measures, the present study may aid in precision medicine and informed pharmacotherapy.